1999
DOI: 10.1111/j.1528-1157.1999.tb00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes in Neuronal Migration Disorders: Evaluation by Combined MRI and Proton MR Spectroscopy

Abstract: Summary: Purpose: To assess the role of 'H-magnetic resonance spectroscopy (MRS) in detecting biochemical abnormalities in neuronal migration disorders (NMDs).Methods: We performed 'H-MRS studies on 17 brain NMD areas [five polymicrogyria, eight subcortical heterotopia, and four cortical dysplasia on magnetic resonance imaging (MRI)]. The study group consisted of I5 patients, all but one affected by partial epileptic seizures. Spectra were acquired from volumes of interest localized on NMDs and contralateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
22
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 42 publications
9
22
1
1
Order By: Relevance
“…In 11 of these articles, the metabolite ratios obtained in the lesion were compared with those in a control group, and in 9 articles, the NACS was also studied. 9,19,20,[24][25][26][27]29 The abnormality most frequently found in MCD was decreased NAA or NAA/Cr in the lesion compared with a that in the control group, 9,20,[22][23][24]27,28,31 in agreement with our results, but some articles reported cases presenting a normal NAA peak in MCD compared with that in a control group. 21,29,30 This observation might be explained by the fact that these authors used single-voxel MR spectroscopy with a larger voxel volume size (3-8 cm 3 ) than the one used in our study (2.25 cm 3 ).…”
Section: Controls Patientssupporting
confidence: 92%
See 2 more Smart Citations
“…In 11 of these articles, the metabolite ratios obtained in the lesion were compared with those in a control group, and in 9 articles, the NACS was also studied. 9,19,20,[24][25][26][27]29 The abnormality most frequently found in MCD was decreased NAA or NAA/Cr in the lesion compared with a that in the control group, 9,20,[22][23][24]27,28,31 in agreement with our results, but some articles reported cases presenting a normal NAA peak in MCD compared with that in a control group. 21,29,30 This observation might be explained by the fact that these authors used single-voxel MR spectroscopy with a larger voxel volume size (3-8 cm 3 ) than the one used in our study (2.25 cm 3 ).…”
Section: Controls Patientssupporting
confidence: 92%
“…Examinations were not performed within 48 hours of the last seizure, except in 4 patients who had daily episodes. This procedure was adopted because of the previous evidence of the presence of a lactate peak in the spectra of patients with MCD who experienced seizures a short time before MR spectroscopy acquisition, 9 probably reflecting anaerobic glycolysis during and after seizures.…”
Section: Studied Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous article reported that the Cho signal is decreased in the CD area (18). Although the reason for this discrepancy remains unknown, a possible explanation may lie in the difference in the age of the patients.…”
Section: Figmentioning
confidence: 90%
“…Therefore, NAA reductions might also be helpful for a better delineation of structural and functional abnormal regions in CMs and the surrounding normal appearing tissue. This assumption is supported by the fact that the most consistent finding of the limited number of MRS studies in CMs has indeed been a reduction of NAA [6,13,[17][18][19]26,31]. However, considering the fact that MRI visible CMs usually contain abnormal neuronal elements and are characterized by severe disturbances of the histological architecture, metabolic abnormalities are probably not restricted to NAA but affect also creatine/ phosphocreatine (Cr) and choline compounds (Cho).…”
Section: Introductionmentioning
confidence: 99%